2014
DOI: 10.1182/asheducation-2014.1.590
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-associated B-cell non-Hodgkin lymphomas

Abstract: Epidemiological studies have demonstrated an increased risk of developing B-cell lymphomas in patients with chronic hepatitis C virus (HCV) infection. However, the strength of the association shows great geographic discrepancies, with higher relative risk in countries with high HCV prevalence. It remains unclear whether additional environmental and genetic factors are involved or if the international variability is simply a consequence of the variable infection prevalence. Therefore, a causal relationship rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
1
25
0
1
Order By: Relevance
“…Epidemiological studies have demonstrated an increased risk of developing B‐NHL in patients with chronic HCV infection . B‐NHL subtypes frequently associated with HCV are marginal zone lymphoma, lymphoplasmacytic lymphoma, and diffuse large B‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have demonstrated an increased risk of developing B‐NHL in patients with chronic HCV infection . B‐NHL subtypes frequently associated with HCV are marginal zone lymphoma, lymphoplasmacytic lymphoma, and diffuse large B‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…B‐NHL subtypes frequently associated with HCV are marginal zone lymphoma, lymphoplasmacytic lymphoma, and diffuse large B‐cell lymphoma. The most convincing evidence for a causal relationship between HCV infection and lymphoma development is the observation of B‐NHL regression after HCV eradication with interferon‐α monotherapy or in combination with ribavirin . However, the strength of the association shows great geographic discrepancies, with higher relative risk in countries with high HCV prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,66,67 The association with HCV, however, shows considerable and not entirely explained geographic discrepancies. 68 These site-specific biological differences might influence outcome, and recognition of the driving source of the antigenic stimulation in different tissues may have important therapeutic implications. Although antibiotic therapy is nowadays well established for primary gastric MALT lymphoma, much less is known about the value of anti-infectious therapy in other MALT lymphomas (Table 3 69-72 ).…”
Section: Association Of Different Infectious Agents With Malt Lymphommentioning
confidence: 99%
“…Importantly, the strongest evidence for a causal relationship between HCV and lymphoma comes again from the observation of lymphoma regression after antiviral treatment. 68,105,106 Several potential pathogenic mechanisms have been advanced to explain a causative link with lymphoma growth 68,107 : a nondirect antigen-driven stimulation; a direct oncogenic role of HCV; a viral immunosuppressive effect on the tumor cells; and the co-infection by another unknown oncogenic virus.…”
Section: Hcv and Malt Lymphomasmentioning
confidence: 99%